The immune response to airway mycosis. (August 2021) - Li, Evan; Rodriguez, Antony; Luong, Amber U; Allen, David; Knight, John Morgan; Kheradmand, Farrah; Corry, David B
Abstract : The allergic airway diseases chronic rhinosinusitis (CRS), allergic fungal rhinosinusitis (AFRS), asthma, allergic bronchopulmonary mycosis/aspergillosis (ABPM/A), and cystic fibrosis (CF) share a common immunological signature marked by TH 2 and TH 17 cell predominant immune responses, the production of IgE antibody, and a typical inflammatory cell infiltrate that includes eosinophils and other innate immune effector cells. Severe forms of these disorders have long been recognized as being related to hypersensitivity reactions to environmental fungi. Increasingly however, environmental fungi are assuming a more primary role in the etiology of these disorders, with airway mycosis, a type of non-invasive airway fungal infection, recognized as an essential driving factor in at least severe subsets of allergic airway diseases. In this review, we consider recent progress made in understanding the immune mechanisms that drive airway mycosis-related diseases, improvements in immune-based diagnostic strategies, and therapeutic approaches that target key immune pathways.